Enhancing Vocational Higher Education Lecturers’ Pedagogical Competence through a Digital Platform-Based Flipped Classroom - Sarwa; Riansyah Putra; Ahmad Zulfikar; Liana Atika; Mita Dwi Putri; Ridho Azahar (The Indonesian Institute of Science and Technology Research, 2026)
This study aims to analyse the effectiveness of implementing the flipped classroom model using the Moodle and Google Classroom learning management systems in enhancing pedagogical competence and learning management skills. This model is implemented through pre-class, during-class, and post-class learning stages facilitated by digital materials, interactive forums, and automatic evaluation mechanisms on the platform. The research method used a one-group pretest–posttest design with 37 lecturers in the Faculty of Engineering as subjects. Data analysis was performed using a paired sample t-test, one-sample t-test, and N-Gain calculation to assess competency improvement after the intervention. The results showed a significant increase in lecturers' initial and final competencies after participating in the flipped classroom model, as evidenced by a significant value of (p = .00 < .05). The N-Gain value of (.502) was in the moderate category, reflecting a consistent improvement in lecturers' abilities in the aspects of learning design, digital technology utilisation, and feedback provision through the platform. The integration of technology also strengthened the efficiency of classroom management and enabled lecturers to implement more adaptive, collaborative, and vocationally-oriented learning. This research implies that the flipped classroom model can be used as a strategy for developing lecturers’ professional skills in instructional design, the use of digital media, and interactive classroom management, and can serve as a basis for vocational higher education institutions to systematically integrate digital platforms to drive a transformation towards more effective teaching practices.